Characteristics of Monsoon Current Patterns in Maluku Waters in the ENSO Period - Yusran Abdul Gani Tuatoy; Simon Tubalawony; Ronald Darlly Hukubun (Nekton, 2026)
The hydrodynamic conditions of the Maluku waters are highly dynamic and are generally influenced by several oceanographic factors, including current patterns that are also affected by variations in monsoonal winds. At present, global climate change associated with the El Niño–Southern Oscillation (ENSO) phenomenon is suspected to have altered wind and current patterns. This study aims to examine the variations in monsoonal wind patterns and monsoonal current patterns during ENSO events in the Maluku waters, including the Seram Sea, Banda Sea, and Arafura Sea. Monthly averaged wind and current data were obtained from the Copernicus database, while ENSO index data were acquired from the National Oceanic and Atmospheric Administration (NOAA) database. The results indicate that the average maximum wind speed during the West Monsoon reaches 6.1 m/s with a southeastward direction, whereas during the East Monsoon it reaches 9.2 m/s with a northwestward direction. Based on the direction of movement, the prevailing winds are characterized as monsoonal winds. The average maximum current velocity during the West Monsoon reaches 0.8 m/s with an eastward direction, while during the East Monsoon it reaches 1.4 m/s with a dominant westward movement. The dominant direction of current movement generally follows the direction of the monsoonal winds. The influence of ENSO indicates that the average wind speed and spatial distribution of winds increase during El Niño events, whereas the average current velocity and spatial distribution of currents increase during La Niña events.